Cultura starter produzida em meio de cultura de plasma suíno e antioxidante natural na elaboração do salame - Campagnol, Paulo Cezar Bastianello (2007)
This work aimed to produce and to apply in dry fermented sausage a lactic acid starter culture using a pork plasma culture medium and to evaluate the effect of two levels (0.5% and 1%) of hydroalcoholic extract of marcela (Achyrocline satureioides) in the security and quality of dry fermented sausages. In the first experiment, the microorganism Lactobacillus plantarum was fermented with control of pH, during 36 hours, under continuous agitation of 100 rpm, at a temperature of 37 (± 0.1ºC). After entering in the stationary phase the culture was lyophilizated and applied in dry fermented sausage, evaluating its influence in the microbiological, physico-chemical and sensorial characteristics. For comparative effects, were elaborated treatments without addition of starter culture and with addition of a commercial culture. In the second experiment, dry fermented sausages had been elaborated with 0.5% and 1% of hydroalcoholic extract of marcela and without extract, considered as control. The parameters of pH, water activity, colour and weight loss were evaluated during the manufacture of the dry fermented sausages. During the storage the TBARS values were determined and verified the sensorial acceptance. The microorganism Lactobacillus plantarum had a maximum growth of 9.82 Log UFC.mL-1, after 30 hours of fermentation and it presented 90.05% of survival to the lyophilization. The dry fermented sausages elaborated with the starter culture produced had presented a decrease on pH significantly faster and a lower water activity than the others treatments. Moreover, the microorganism Lactobacillus plantarum improved significantly the flavor of the dry fermented sausages. The marcela extract addition decreased (p<0.05) the TBARS values during the storage of the dry fermented sausages, compared with the control. The treatment with 1% of marcela extract showed a bigger lipid stability than that with 0.5%, however it presented a reduction (p<0.05) in the sensorial acceptance. The two marcela extract levels had not influenced the parameters of pH, water activity, colour and weight loss. Therefore, this study indicated that the pork plasma culture medium is an alternative in the commercial production of lactic acid bacteria and that the starter culture produced provided a dry fermented sausage with greater microbiological security and better sensorial acceptance. The hydroalcoholic extract of marcela decreased the lipid oxidation and the concentration of 0.5% did not modify the sensorial characteristics, being able, therefore, to be used in the elaboration of safer dry fermented sausages to the consumers.